2013
DOI: 10.1111/jpc.12262
|View full text |Cite
|
Sign up to set email alerts
|

Use of intravenous immunoglobulin in an Asian paediatric population over a 10‐year period

Abstract: Albeit substantial and increasing, the use of IVIG in Singaporean children is mostly evidence based.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…This value is much higher than those reported in the other studies. A study conducted in Singapore over a 10-year period in two public pediatric hospitals reported that IVIG was used for off-labeled indications in only less than 25% of cases (Wu et al, 2013). A study on IVIG use in the 10 institutions in Canada from 1997 to 1999 found that 38% of children received IVIG for offlabeled indications (Hanna et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This value is much higher than those reported in the other studies. A study conducted in Singapore over a 10-year period in two public pediatric hospitals reported that IVIG was used for off-labeled indications in only less than 25% of cases (Wu et al, 2013). A study on IVIG use in the 10 institutions in Canada from 1997 to 1999 found that 38% of children received IVIG for offlabeled indications (Hanna et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, this value is much higher than those reported in the other studies. A study conducted in Singapore over a 10-year period in two public paediatric hospitals reported that IVIG was used for off-labelled indications in only less than 25.0% of cases, while in Qatar, only 22.7% of children received IVIG for off-labelled indications ( 18 , 19 ). These variations can result from a variety of causes, such as the incidence of disease in different countries, varying patient conditions, and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…Similar prescribing pattern studies have been conducted in several countries and the prevalence of prescriptions with off-label indications of IVIG ranged from 22.7 to 70.3% ( Rezaie et al, 2019 ; Tonkovic and Rutishauser, 2014 ; Toh et al, 2014 ; Ruiz-Antorán et al, 2010 ; Constantine et al, 2007 ; Pendergrast et al, 2005 ; El Ajez et al, 2019 ) ( Supplementary Table S3 ). Likewise, the prevalence of patients being prescribed with IVIG for an off-label indication ranged from 23.2 to 81.5% ( Chen et al, 2000 ; Pendergrast et al, 2005 ; Dawoud et al, 2012 ; Wu et al, 2013 ; Fakhari et al, 2018 ; Rezaie et al, 2019 ). The wide range could be due to different categorization or interpretation of off-labels, study periods, or duration of data collection, as licensing of an indication may change over time with the availability of more studies supporting its use.…”
Section: Discussionmentioning
confidence: 99%
“…These results corroborate the findings by ( Fakhari et al, 2018 ), whereby older age patients were more likely to receive IVIG for an off-labeled indication. Noticeably, the studies of IVIG utilization conducted for pediatric usage were mostly for FDA-licensed indications ( Wu et al, 2013 ; Aydin and Tanır, 2017 ; El Ajez et al, 2019 ). It appears that IVIG is more likely to be tested out for new indications in adult diseases.…”
Section: Discussionmentioning
confidence: 99%